2012
DOI: 10.1186/1752-1947-6-33
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous endovascular repair of an iatrogenic carotid-jugular fistula and a large iliocaval fistula presenting with multiorgan failure: a case report

Abstract: IntroductionIliocaval fistulas can complicate an iliac artery aneurysm. The clinical presentation is classically a triad of hypotension, a pulsatile mass and heart failure. In this instance, following presentation with multiorgan failure, management included the immediate use of an endovascular stent graft on discovery of the fistula.Case presentationA 62-year-old Caucasian man presented to our tertiary hospital for management of iatrogenic trauma due to the insertion of a central venous line into his right co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Seven patients were managed conservatively, and 6 of these endoleaks sealed spontaneously. 9,11,12,[16][17][18]20 There was a persistent flow over the ACF with shrinkage of the aneurysm sac in 1 patient at the 2-year follow-up. 20 The other 5 patients with type 2 endoleaks underwent intervention.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Seven patients were managed conservatively, and 6 of these endoleaks sealed spontaneously. 9,11,12,[16][17][18]20 There was a persistent flow over the ACF with shrinkage of the aneurysm sac in 1 patient at the 2-year follow-up. 20 The other 5 patients with type 2 endoleaks underwent intervention.…”
Section: Discussionmentioning
confidence: 97%
“…From 1998 to 2015, 17 articles reported on 17 patients presenting with endoleaks after endovascular stent-grafting of ruptured AAA with an ACF (Table 2). 2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The site of the fistula was the aortocaval segment in 14 (82%) patients and iliocava segment in 3 (18%) patients. The most common endoleak was type 2 endoleak, which occurred in 12 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an ilio-iliac AVF presenting with systematic symptoms is rare. 1,11 We searched literatures since 1999 by using PubMed, and found only two patients with ilio-iliac AVF presenting multi-organ dysfunction. 10,12 However, both of them had an extensive fistula orifice, which demonstrated that ilio-iliac AVF may be fatal with specifically unfavorable anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The severe venous hypertension and congestive heart failure can cause pulmonary arterial hypertension, which lead to pneumoedema and respiratory failure. 1012 In such patients, acute renal failure may occur as a result of unusual high renal congestion due to venous hypertension. 13,14 Furthermore, heart failure and associated hypoperfusion may lead to pre-renal failure.…”
Section: Discussionmentioning
confidence: 99%